Public Understanding of The Mechanism for Administering State Administrative Courts as a Form of Legal Protection - Marsheila, Wiwin; Hakim, Sholihul (Universitas Tidar, 2023)
Legal relations in social life are part of the process after the emergence of a legal action originating from the legal subject itself. Legal action is the beginning of the birth of legal relations (rechtsbetrekking), namely interactions between legal subjects that have legal relevance. One of them is the relationship between the government and citizens. The government, as an executor (public servant), obtains broad authority in carrying out government affairs (Constitutional Mandate). This authority is likely to be abused, causing harm and injustice (Power Tends Corrupt, Absolute Power Corrupts Absolutely). The State Administrative Court is present as an institution that provides legal protection to the justice-seeking public related to administrative law (Administrative Law). This court has a tiered system starting from the first level, the appeal level, and the final level or cassation. The legal issues that will be discussed in this paper concern phenomena in the administration of the State Administrative Court in Indonesia, such as the court process, the basis for a lawsuit addressed to the government, and the mechanism in the State Administrative Court.